East Asian Economic Regionalism Feasibilities and Challenges - Ahn, Choong Yong.; Ahn, Choong Yong.; Baldwin, Richard E.; Baldwin, Richard E.; Cheong, Inkyo.; Cheong, Inkyo. (Springer US : Imprint: Springer, 2005)
Economic regionalism has become a worldwide phenomenon. Since the Asian financial crisis, East Asian countries are accelerating the ongoing market-driven economic integration as well as institutional economic integration. The question is whether East Asia can reach an East Asian FTA (EAFTA), which is the first step towards institutional economic integration. East Asian Economic Regionalism attempts to analyze the feasibilities of economic integration in East Asia and to discuss emerging economic integration efforts in East Asia with special reference to an East Asian FTA. Although economic integration is desirable economically, positions and approaches of each regional economy toward East Asian economic integration may differ depending on the circumstances of the countries concerned. East Asian Economic Regionalism provides diverse positions on East Asian economic integration by ASEAN countries, as well as the Northeastern countries of China, Japan and Korea. The volume also provides economic assessment of EAFTA and evaluates East Asian economic integration. East Asian Economic Regionalism may be the first book on East Asian economic integration with positions toward economic integration of major players in the region.